I am a Muslim and Asian Woman in the United Kingdom: Living Comfortably in an Uncomfortable Situation - Pazil, Nur Hafeeza Ahmad (Journal of International Students, 2022)
Utilizing an autoethnographic stance and method, this article is based on my experiences as a Malaysian postgraduate student in the United Kingdom. I draw upon my memories of dealing with Islamophobia and xenophobia while living there, as a Muslim and Asian woman. Anti-Asian sentiment and xenophobia can be experienced in many forms, ranging from feelings of discomfort to verbal insults and direct confrontation. As a visible Muslim and Asian woman, I reflect upon my own experience as a victim of verbal abuse on different occasions. This article offers an intersectional perspective taking into account interconnected and overlapping factors, such as gender, ethnicity and religion, to examine the multi-layered issues and challenges as an international student. I highlight the challenges in expressing and negotiating my intersectional identities while living temporarily abroad. Therefore, this article is important to raise awareness about Islamophobia as well as inadvertent or deliberate xenophobia towards Asian communities.